Reflexiones sobre la creación de la primera clínica de abogacía comunitaria en Puerto Rico - Morales-Cruz, Myrta (2013)
This essay focuses on the creation of the first community-based advocacy clinic in Puerto Rico. Different community lawyering approaches are discussed, with an emphasis on clinical legal education and its contribution to the training of legal professionals.